2006
DOI: 10.1049/ip-cdt:20050182
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating molecular dynamics simulations with configurable circuits

Abstract: Molecular Dynamics (MD) is of central importance to computational chemistry. Here we show that MD can be implemented efficiently on a COTS FPGA board, and that speedups from ¿½¢ to ¢ over a PC implementation can be obtained. Although the amount of speed-up depends on the stability required, ¢ can be obtained with virtually no detriment, and the upper end of the range is apparently viable in many cases. We sketch our FPGA implementations and describe the effects of precision on the trade-off between performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 21 publications
(18 reference statements)
0
53
0
Order By: Relevance
“…The system uses the x G y 6 method to find interacting pairs. [7] is another work in which the entire velocity Verlet algorithm is considered. This work is similar to [3] in that both implementations perform all steps of the algorithm in hardware using fixed-point arithmetic, only nonbonded force calculation is implemented, this nonbonded force calculation is performed with table lookup and interpolation, and, it seems, the interaction pairs are found using the x H y 6 approach.…”
Section: Comparison To Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The system uses the x G y 6 method to find interacting pairs. [7] is another work in which the entire velocity Verlet algorithm is considered. This work is similar to [3] in that both implementations perform all steps of the algorithm in hardware using fixed-point arithmetic, only nonbonded force calculation is implemented, this nonbonded force calculation is performed with table lookup and interpolation, and, it seems, the interaction pairs are found using the x H y 6 approach.…”
Section: Comparison To Related Workmentioning
confidence: 99%
“…This hardware/software approach to acceleration is the key to developing a more complete simulation system than previous acceleration efforts that moved all tasks of the simulation into hardware [3,7]. It takes into account the fact that not all tasks in a large scientific program, such as a program for MD simulation, are good candidates for acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…9 We have found that the acceleratable kernel not only comprises more than 90 percent of execution time with ProtoMol, but the modularity enables straightforward integration of an FPGA accelerator. 10 …”
Section: Methods 4: Living With Amdahl's Lawmentioning
confidence: 99%
“…While most MD applications require more than the 24 bits provided by a single-precision floating point, they might not need double precision (53 bits). 10 Sample HPC/FPGA solution-We return to the modeling molecular interactions case study to illustrate the tradeoff between PE complexity and degree of parallelism. That study examined six different models describing intermolecular forces.…”
Section: Methods 8:use Appropriate Arithmetic Precisionmentioning
confidence: 99%
“…All these hardware systems are specialized ASIC based solutions for specific N-body applications. Reconfigurable systems utilizing FPGAs have been developed in [23], [24], [25], [26], [27]. Most of them are also customized for a particular interaction function.…”
Section: Scientific Application: N-body Problemsmentioning
confidence: 99%